THE EFFECT OF SUPPORT ON THE ACTIVITY AND SELECTIVITY OF MoVNbTe CATALYST FOR PROPANE AMMOXIDATION REACTION - Ramli, Anita; M. Jamil, Farinaa; M. Ibrahim, Suhaina (ANALIS, 2007)
MoVNbTe catalyst has been prepared using slurry method for the ammoxidation of propane to acrylonitrile (ACN). To study the effect of support on the catalytic activity of this catalyst, 10% (wt/wt) of MoVNbTe was loaded to silica (SiO2), alumina (Al2O3) and magnesia (MgO) via incipient wetness impregnation method. All MoVNbTe catalysts were calcined in air at 350-600 oC for a total of 10 h. The textural, morphological and microstructural characteristics of these catalysts were determined using scanning electron microscopy, X-ray Diffraction (XRD) and physical adsorption of Nitrogen gas. The catalytic activity of all catalysts was tested using a fixed-bed reactor with online GC at 420 oC. Results show that the physicochemical properties of these catalysts are greatly influenced by the support used.